The role of ChatGPT in developing systematic literature searches: an evidence summary - Parisi, Veronica; Sutton, Anthea (Journal of EAHIL, 2024)
This evidence summary explores the potential and limitations of using ChatGPT for developing systematic literature searches. A systematic search identified the current peer-reviewed and grey literature. Studies were selected according to eligibility criteria. Included studies were analysed and synthesised narratively, focusing on the strengths, limitations, and recommendations for using ChatGPT to assist with the systematic literature searching process. Current literature is mostly opinion-driven, and there is limited published literature originating from the library and information profession. At present, limitations outweigh the strengths of ChatGPT for systematic literature searching, caution should be exercised, and human oversight is essential. More research is required, and information specialists and librarians are in a prime position to develop guidelines and share examples of best practice.